Implementasi Algoritma Gredy untuk Rekomendasi Objek Wisata di Pulau Nias Berbasis Website - Rejeki Ndruru; Yessi Fitri Annisah Lubis (LKP KARYA PRIMA KURSUS, 2025)
Tourism in Nias Island has great potential with a variety of attractions, including natural, cultural, and historical destinations. However, tourists often face difficulties in selecting the most suitable tourist spots according to their time, distance, and preferences. This research aims to develop a web-based tourism recommendation system by implementing the Greedy algorithm. The algorithm is applied to determine the sequence of tourist site visits by iteratively choosing the shortest distance, thus minimizing travel time. The system development method used is the Waterfall model, which includes requirements analysis, design, implementation, and testing. The testing results show that the system can provide more efficient travel route recommendations compared to manual selection, with consistent accuracy. In conclusion, the implementation of the Greedy algorithm in this recommendation system can assist tourists in planning their trips in Nias Island more effectively and efficiently.